Rapid Sequence Spinal pada Seksio Sesarea Emergensi - Adiyanto, Bowo; Widodo, Untung; Wibowo, Arif Setyo (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Obstetric emergencies are a challenge both for the obstetrician and the anesthesiologist. The incidence of caesarean sections as per the National Family Health Survey published in 2015–16 was 17.2%. In 7.6% of cases, the decision to conduct a caesarean section was taken after the onset of labour pain. Caesarean sections are classified depending on the urgency into four categories. The target decision to delivery interval for category 1 caesarean section is less than 30 min. The management of these emergencies involves a rapid assessment with minimal investigations. Although general anaesthesia is considered to have higher morbidity and mortality, category 1 caesarean sections may still warrant this technique. Rapid sequence spinal anaesthesia is replacing general anaesthesia for category 1 SC emergency. In category 2 and 3 caesarean sections, spinal anaesthesia still remains the technique of choice